INTENSIVE MICRO COACHING CLINIC: MEMBUKA KESADARAN FENOMENOLOGIS GURU SD BEKASI DALAM MENGOPTIMALKAN PROGRAM GURU PENGGERAK - Awiria, Awiria; Jamaludin, Ujang; Fathurrozi, Ahmad; Dalilah, Evi; Alfianto, Fauzan Dwi; Salsabila, Sabrina Putri (LPPM Universitas Bina Bangsa, 2024)
The Teacher Leader Program aims to enhance the quality of education through the professional development of teachers. At elementary schools in Bekasi, the primary challenge is to boost teachers' motivation and active involvement in the implementation of this program. The Intensive Micro Coaching Clinic is designed to increase teachers' phenomenological awareness deep understanding of their needs and experiences in developing their professionalism through the series of activities in the Teacher Leader Program. Through intensive coaching, participants receive direct support and motivation to engage fully in the Teacher Leader Program. The success of this training is measured by: 1) The improvement in participants' motivation and involvement in the program, 2) Achievement of training goals that support active participation, and 3) Application of training material directly in the involvement with the Teacher Leader Program. With this approach, it is hoped that teachers' skills and leadership will be significantly developed, leading to effective teaching methods, motivated students, and a positive learning culture at elementary schools in Bekasi through the Teacher Leader Program